The effect of different molarity on CuO thin films using sol gel dip coating method / Muhammad Umar Shahbuddin - Shahbuddin, Muhammad Umar (2016)
The thesis is about the effect of different molarity on copper (II) oxide (CuO) thin films using sol-gel dip-coating technique. The CuO thin films were deposited on glass substrate by sol-gel process dip-coating method. The objective of the research was to investigate the effect of the different molar concentration on the surface of morphology and electrical optical properties of the thin films. The molar concentration of CuO thin films used for this experiment was 0.3M, 0.35M, 0.4M, 0.45M and 0.5M. These concentrations were prepared using sol-gel method where the solutions were formed by dissolving the copper (II) acetate powder in the solution, the mixture of isopropyl, diethanolamine (MEA) and polyethyleneglycol (PEG). The samples were dried for five minutes at 250°C and annealed in furnace for one hour at 450°C. Field Emission Scanning Electron Microscopy (FESEM) was used to characterize the surface morphology of the samples. The films surfaces of the samples were smooth and the grains were evenly distributed. The measurement of the average grain size of the samples were taken from the FESEM images and tabulated. UV-Vis spectrometer was used to obtain the measurement of transmittance and the absorption of the samples. The transmittance and absorbance were measured within the wavelength range of 300nm to 800nm. From the obtained measurement, the graph of both parameters were plotted. From the graph, the absorption is decreases as the molarity is increased. The transmittances of the samples were increased as the concentration of the solution increase. The solar simulator was used to measure the electrical properties. The current and voltage were directly proportional to each other. The resistivity and conductivity were calculated using formula using the I-V measurement from the solar simulator. The graphs of both resistivity and conductivity were plotted against the molar concentarion. As the molar concentration increases, the resistivity was decreases. The conductivity was opposed the resistivity which it is increases as the molar concentration increased. The different molar concentration is one of the factors that should be taken in order to make good devices.